The relationships among perceived league product quality, spectator satisfaction, trust, team identification, and loyalty in the Chinese Super League - Fei Liu; Sisi Wu; Jingyin Zhou; Mu Fan; Fengqin Tian (PLoS ONE, 2026)
Objective This study integrates perceived league product quality, spectator satisfaction, trust, team identification, and loyalty into a unified analytical framework to examine their relationships, thereby providing empirical evidence to inform more effective marketing strategies for the Chinese Super League (CSL). Methods Guided by the ABC attitude model and conceptual definitions, as well as prior research, the study develops a theoretical model and an initial pool of measurement items. Expert consultation and a pilot study were subsequently conducted to refine items. On-site questionnaires were administered to the CSL spectators, yielding 320 responses, of which 278 were valid. Data were analyzed using SPSS 22.0, AMOS 23.0, and PROCESS v4.2 to assess scale reliability and validity, evaluate the structural model fit, and test path coefficients and mediation effects. Results The theoretical model demonstrated a good fit to data, path analysis revealed that perceived league product quality had significant positive effects on satisfaction (β = 0.759, p < 0.01), trust (β = 0.540, p < 0.01), and team identification (β = 0.570, p < 0.01), but not on loyalty (β = 0.205, p > 0.05). Satisfaction (β = 0.038, p > 0.05) and trust (β = 0.029, p > 0.05) did not significantly affect loyalty, whereas team identification had a significant positive effect on loyalty (β = 0.534, p < 0.01). Mediation analysis indicated that the indirect effects of league product quality on loyalty, mediated by satisfaction and trust, were not significant, whereas the indirect effect through team identification was significant. Furthermore, a chain mediation pathway of league product quality → Satisfaction → Team Identification → Loyalty was found to be statistically significant. Conclusion Higher perceived league product quality significantly enhances spectator satisfaction, trust, and team identification. Among these factors, team identification emerges as the strongest predictor of spectator loyalty and serves as the primary mediating mechanism through which perceived league product quality is translated into sustained spectator loyalty.